Serum Mediators in Patients with Both Type 2 Diabetes Mellitus and Pruritus - Guan-Yi He; Tai-Yi Hsu; Ching-Wen Chen; Feng-Jung Nien; Huan-Yuan Chen; Chia-Yu Chu; Li-Fang Wang (Medical Journals Sweden, 2023)
Chronic pruritus is an unpleasant sensory perception that negatively affects quality of life and is common among patients with type 2 diabetes mellitus. Current antipruritic therapies are insufficiently effective. Thus, the mediation of diabetic pruritus by histamine-independent pathways is likely. The aim of this study was to identify possible mediators responsible for diabetic pruritus. A total of 87 patients with type 2 diabetes mellitus were analysed, of whom 59 had pruritus and 28 did not. The 2 groups were assessed for baseline demographics, serum biochemistry parameters, cytokines, and chemokines. This study also investigated the associations of these factors with the severity of itching. Neither haemoglobin A1c nor serum creatinine levels were correlated with severity of itching. Significantly higher levels of interleukin-4 (p = 0.004), interleukin-13 (p = 0.006), granulocyte-macrophage colony-stimulating factor (p < 0.001) and C-X-C motif chemokine ligand 10 (p = 0.028) were observed in the patients with pruritus than in those without pruritus. Moreover, the levels of these mediators were positively correlated with the severity of itching. Thus, novel antipruritic drugs can be developed to target these molecules. This is the first study to compare inflammatory mediators comprehensively in patients with diabetes mellitus with pruritus vs those without pruritus.